REMODELLING MUSHARAKAH MUTANAQISHAH CONCEPT: CASE HOME EQUITY REFINANCING - Hardiansyah, Hardiansyah; Septiano Abdillah Baysonni,; Wirman, Wirman; Ade Wirman,; Ade Ananto Terminanto, (Journal of Innovation Research and Knowledge, 2025)
This paper aims to remodel musharakah Mutanaqishah to transform your home equity into real wealth without taking on debt and riba-free, compared with the existing Musharakah Mutanaqishah (MMQ) in the Islamic Financial Institution (IFI) model. This study uses secondary data and Islamic literature. We use simulation data to explain the proposed model. The calculation will be based on the risk-adjusted cost of capital for the capital eligible to finance. The results show that this proposed model through Islamic Finance can be an alternative financing method due to its ease and reliability, especially for Islamic fintech, which has a different business model from banking